Improving Human Development Index (HDI) through Education Spending in Bogor Regency - Lugina, Sammy; Sutrisno, Edy (Yayasan Riset dan Pengembangan Intelektual, 2025)
The improvement of the Human Development Index (HDI) in the education dimension heavily relies on the achievements of Expected Years of Schooling (EYS) and Mean Years of Schooling (MYS). Bogor Regency, one of the most populous regions in Indonesia, faces critical challenges in accelerating progress in both indicators. This study aims to analyze the underlying factors of the suboptimal improvement in EYS and MYS through local government spending and to formulate appropriate strategies to enhance the effectiveness and equity of education budget allocation. The research employs a mixed-methods approach using descriptive analysis, SWOT, and the Analytical Hierarchy Process (AHP). Data collection was conducted through document review, in-depth interviews with key informants, and structured AHP-based questionnaires administered to local stakeholders. The findings reveal that the unequal distribution of secondary schools, shortage of civil servant teachers, and limited access to education in remote areas are the primary constraints. The AHP analysis identifies internal weaknesses as the most influential factor hindering educational outcomes. Strategic recommendations emphasize the equitable development of junior secondary schools, capacity-building and equitable placement of teachers, and the advancement of spatial data-driven budget planning systems. The results underscore the necessity for cross-sectoral integration and stakeholder engagement in evidence-based education policy formulation. This study contributes to the development of a more adaptive, participatory, and outcome-oriented strategic framework for regional education development aimed at enhancing the quality of human capital.